شكالية حماية الشركات من الإفلاس في القانون الجزائري - مفتاح, براشمي (University of El oued, 2020)
تلعب الشركات التجارية دورا أساسيا في اقتصاديات الدول؛ فإذا تعرضت للّفاس انعكس ذلك سلبا على مختلف املصالح؛ لهذا لجأت أغلب الدول املتطورة إلى تبني قوانين وقائية قصد تفادي إفاسها، على غرارّ الجزائر باعتبارها تبنت النظام االقتصادي الحر )املعتدل(؛ الّمر الذي ستتديي تأسيس أطر تشريعية من شأنها حماية هذه الشركات من الّفاس وإتخاذ إجراءات تخول الشعار عن تجاوزات الشركة، وّسوء استغال أموالها، وّكذلك حمايتها في حال واجهت صعوبات مالية، وّانقاذها من التصفية. إضافة إلى ضرورة حماية مختلف أصحاب املصالح في الشركة أثناء إجراءات الّفاس وّتحميل مديريها متؤولية أخطائهم. Abstract: Companies play an important role in the economies of countries, but in case of bankruptcy, different interest will be deeply affected. Therefore, most developed countries have adopted preventive laws in order to avoid its bankruptcy. Algeria, adopted the moderate liberal economic system. In this context, laws should be instituted to protect these companies from bankruptcy. Besides, procedures must be taken so as to authorize the alert of the company's excesses and misuse of its funds and in case it faces financial difficulties which will save it from liquidation. Moreover, it is necessary to protect the company’s stakeholders during bankruptcy proceedings, and hold its managers responsible for their
مجلة العلوم القانونية ، الجلد 11 ،العدد 01 ، جامعة الوادي
Keywords: وقاية الشركة من الّفاس؛ حماية الشركة املفلتة؛ املتؤولية.; Bankruptcy prevention; protecting the bankrupt company